2020
DOI: 10.1111/aje.12717
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution patterns of aquatic macrophytes in selected ecosystems of south western Nigeria

Abstract: The present study investigates the macrophytes diversity from selected aquatic ecosystems in South‐Western Nigeria using quadrat method. The survey revealed two major aquatic ecosystem types (mangrove and freshwater swamp) and recorded a total of 83 species belonging to 77 genera and 41 families. Three species (Sacciolepis africana, Ipomoea asarifolia and Commelina diffusa) were found present in all the surveyed areas. However, species such as Acrostichum aureum, Avicennia germinans and Rhizophora racemosa wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
2
6
1
Order By: Relevance
“…In line with previous studies (Kumar & Chelak, 2015; Elo et al, 2018; Oyebanji et al, 2020), we recorded core freshwater species such as A. cordifolia , Costus afer Ker Gawl., Cyperus spp., L. senegalensis , Eichhornia crassipes (Mart.) Solms, Ludwigia spp.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In line with previous studies (Kumar & Chelak, 2015; Elo et al, 2018; Oyebanji et al, 2020), we recorded core freshwater species such as A. cordifolia , Costus afer Ker Gawl., Cyperus spp., L. senegalensis , Eichhornia crassipes (Mart.) Solms, Ludwigia spp.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it adds to the existing knowledge and provides useful information towards the conservation of the habitats and their threatened species. Congruent with previous studies, we identified freshwater swamp and mangrove swamp forest in the LCE (Adekunle, 2006; Adeniyi et al, 2016; Adeonipekun et al, 2019; Ajikah et al, 2019; Obiefuna et al, 2013; Okorie, 2012; Olowokudejo & Oyebanji, 2016; Onyekwelu et al, 2008; Oyebanji et al, 2020). However, the total number of species recorded was lower compared to previous ecological survey of some selected coastal ecosystems in Southern Nigeria (Durugbo et al, 2012, 472 species; Olowokudejo & Oyebanji, 2016, 147 species).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Species presence and absence were recorded for each sampled plot, followed by the comparative floristic analyses of the two zones (IZ and CZ) using four descriptive statistics and diversity indices (Patel et al, 2012, Patel et al, 2020Oyebanji et al, 2020). The descriptive statistics include frequency (%), relative frequency (%), density (plant/m 2 ), and relative density (%) while the diversity indices were performed using Dominance, Evenness, Shannon-Wiener, and Simpson's indices (Simpson, 1949;Shannon and Weaver, 1963;Magurran, 1988) incorporated in Paleontological Statistical software (PAST v 2.17c, Hammer et al, 2001).…”
Section: Discussionmentioning
confidence: 99%